Electrocatalytic composite electrode and preparation method and application thereof

By adsorbing magnetic composite metal oxide particles on the electrocatalytic composite electrode, the stability and cost problems existing in the process of electrocatalytic nitrate reduction and synthesis of ammonia are solved, and an efficient and stable catalytic effect is achieved.

CN119392287APending Publication Date: 2025-02-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310923094.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional precious metal catalysts have obvious hydrogen evolution side reactions, low stability and adsorption performance, and high prices in the process of electrocatalytic nitrate reduction and ammonia synthesis, which limits their large-scale application.

Method used

Magnets are used to adsorb magnetic composite metal oxide particles (FeaCobMcO4, M is Cr, Mn, Ni or Cu) on the surface of the main electrode to form an electrocatalytic composite electrode to improve catalytic activity and stability.

Benefits of technology

Through the adsorption of magnetic composite metal oxide particles, catalytic active sites are increased, the catalytic activity, stability and catalytic life of the electrocatalytic composite electrode are improved, and the preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392287A_ABST
    Figure CN119392287A_ABST
Patent Text Reader

Abstract

The invention relates to an electro-catalytic composite electrode and a preparation method and application thereof, and the electro-catalytic composite electrode comprises a main electrode, a magnet located on one side of the main electrode, and magnetic composite metal oxide particles located on the other side of the main electrode. The magnetic composite metal oxide particles are adsorbed on the surface of the main electrode through the magnetic action of the magnet; the chemical formula of the magnetic composite metal oxide particles is FeaCobMcO4, and M is Cr, Mn, Ni or Cu. The electrocatalytic composite electrode has good electrocatalytic activity and stability and long catalytic life, the preparation process is simple, the cost is low, and the electrocatalytic composite electrode has wide market application prospects when applied to electrocatalytic nitrate reduction synthesis ammonia reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of electrocatalysis technology, and in particular, to an electrocatalytic composite electrode and a preparation method and application thereof. Background Art

[0002] Ammonia (NH3) is an important chemical that can be used as fertilizer, fuel or chemical raw material, and plays a huge role in agriculture, medicine, chemical industry and other industries. In industry, ammonia is mainly prepared by the Haber-Bosch method, using hydrogen and nitrogen as raw materials through a high temperature and high pressure process. However, this method has high energy consumption, dangerous reactants, and the greenhouse gases emitted are not conducive to the environment. Therefore, it is urgent to develop a cleaner and more efficient alternative method. At the same time, with the development of industrialization, a large amount of nitrate is discharged into the environment, causing environmental pollution, destroying the natural nitrogen cycle, and posing a serious threat to animals and plants.

[0003] At present, by applying a certain voltage to the reaction electrode by electrochemical method, nitrate can be reduced to generate ammonia on the cathode surface, wherein the electric energy required for the reaction can be converted from renewable energy such as wind energy, solar energy and tidal energy. Compared with the traditional Haber-Bosch method, the electrocatalytic method has a good application prospect in the degradation of nitrate waste due to its mild reaction conditions, environmental friendliness, high efficiency and excellent economy. Therefore, it is of great research value to prepare highly active, highly stable and efficient catalysts for electroreduction of nitrate to synthesize ammonia. However, the traditional noble metal catalysts (such as platinum, rhodium, ruthenium, etc.) have obvious hydrogen evolution side reactions during the reaction process, low stability and adsorption performance, and high prices, which limit their large-scale application. Therefore, in recent years, a large number of studies have begun to focus on the development of transition metal oxide catalysts. Among them, the problem of poor catalyst life has never been fundamentally solved. Summary of the invention

[0004] The purpose of the present disclosure is to provide an electrocatalytic composite electrode and a preparation method and application thereof to improve the catalytic activity and life of the electrode.

[0005] In order to achieve the above-mentioned object, the present disclosure provides an electrocatalytic composite electrode in the first aspect, which comprises a main electrode, a magnet located on one side of the main electrode, and magnetic composite metal oxide particles located on the other side of the main electrode, wherein the magnetic composite metal oxide particles are adsorbed on the surface of the main electrode by the magnetic force of the magnet; the chemical formula of the magnetic composite metal oxide particles is Fe a Co b M c O4, wherein M is Cr, Mn, Ni or Cu, and a+b+c=3.

[0006] Optionally, M is Cr, a=b=c=1.

[0007] Optionally, based on the unit area of ​​the main electrode, the content of the magnetic composite metal oxide particles is 1 to 30 mg / cm 2 .

[0008] Optionally, based on the unit area of ​​the main electrode, the content of the magnetic composite metal oxide particles is 3-10 mg / cm 2 .

[0009] Optionally, the main electrode is at least one selected from a foamed Ni electrode, a Ni sheet electrode, a foamed Ni / Cu electrode, a foamed Cu electrode and a Cu sheet electrode.

[0010] Optionally, the magnet is an annular magnet, the main electrode is an annular electrode matching the shape of the annular magnet, and the annular electrode is located on the inner side of the annular magnet.

[0011] In a second aspect of the present disclosure, a method for preparing the electrocatalytic composite electrode according to the first aspect of the present disclosure is provided, the method comprising:

[0012] respectively obtaining a magnet, a main electrode and magnetic composite metal oxide particles;

[0013] Attaching the magnet to the outside of the electrolytic cell, and placing the main electrode at the same position inside the electrolytic cell, so that the main electrode is adsorbed on the inner wall of the electrolytic cell by the magnetic force of the magnet;

[0014] The magnetic composite metal oxide particles and a solvent are added into the electrolytic cell, and under stirring conditions, the magnetic composite metal oxide particles are adsorbed on the surface of the main electrode by the magnetic force of the magnet.

[0015] Optionally, the preparation steps of the magnetic composite metal oxide particles include:

[0016] Obtain a mixed solution containing metal ions, wherein the metal ions include Fe 3+ 、Co 2+ and metal M ions, M being Cr, Mn, Ni or Cu;

[0017] The mixed solution is heat-treated to obtain magnetic composite metal oxide particles.

[0018] Optionally, the mixed solution further contains an auxiliary agent, and the molar ratio of the metal ion to the auxiliary agent is 1:(0.1-6); the auxiliary agent is at least one selected from urea, sodium dodecyl sulfate, ammonium chloride and sodium sulfate;

[0019] In the mixed solution, the total concentration of the metal ions is 1 to 40 mmol / L;

[0020] The heat treatment conditions include: temperature of 110-200° C. and time of 2-24 hours.

[0021] In a third aspect of the present disclosure, there is provided application of the electrocatalytic composite electrode described in the first aspect of the present disclosure in electrocatalytic production of ammonia.

[0022] Through the above technical scheme, the electrocatalytic composite electrode disclosed in the present invention uses a magnet to uniformly and tightly adsorb the magnetic composite metal oxide particles on the main electrode surface, thereby bringing more catalytic active sites, having good electrocatalytic activity, stability and long catalytic life. The preparation process of the electrocatalytic composite electrode is simple and low-cost. The electrocatalytic composite electrode is applied to the electrocatalytic nitrate reduction reaction to synthesize ammonia, paving the way for the design and preparation of nitrate reduction catalysts for ammonia production in the future, and has broad market application prospects and huge application value in the synthesis of ammonia industrial products.

[0023] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0025] Figure 1 A schematic diagram of the structure of an electrocatalytic composite electrode according to a specific embodiment of the present invention.

[0026] Figure 2 A schematic diagram of the structure of an electrocatalytic composite electrode according to a specific embodiment of the present disclosure when used in conjunction with an electrolytic cell.

[0027] Figure 3 This is the XRD pattern of the electrocatalytic composite electrode prepared in Example 1.

[0028] Description of Reference Numerals

[0029] 1—main electrode, 2—magnet, 3—magnetic composite metal oxide particles, 4—reference electrode, 5—counter electrode, 6—cation exchange membrane, 7—magneton. DETAILED DESCRIPTION

[0030] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0031] In a first aspect, the present disclosure provides an electrocatalytic composite electrode, Figure 1 The electrocatalytic composite electrode comprises a main electrode 1, a magnet 2 located on one side of the main electrode 1, and a magnetic composite metal oxide particle 3 located on the other side of the main electrode 1. The magnetic composite metal oxide particle 3 is adsorbed on the surface of the main electrode 1 by the magnetic force of the magnet 2. The chemical formula of the magnetic composite metal oxide particle is Fe a Co b M c O4, wherein M is Cr, Mn, Ni or Cu, and a+b+c=3.

[0032] In the chemical formula of the magnetic composite metal oxide particles, a, b, and c represent the atomic numbers of Fe, Co, and M, respectively, and each can be an integer or a non-integer, such as 0.5, 1, or 1.5, as long as the sum of the three is 3.

[0033] In order to further improve the catalytic activity and stability of the electrocatalytic composite electrode, in a preferred embodiment, M is Cr, and a=b=c=1.

[0034] The content of the magnetic composite metal oxide particles can be adjusted within a certain range. Specifically, based on the unit area of ​​the main electrode, the content of the magnetic composite metal oxide particles can be 1 to 30 mg / cm 2 , preferably 3 to 10 mg / cm 2 The particle size of the magnetic composite metal oxide particles can be adjusted within a certain range, for example, 10 to 100 nm.

[0035] The main electrode 1 can be a common electrode material that can be adsorbed by magnetic force in the art, for example, at least one selected from a foamed Ni electrode, a Ni sheet electrode, a foamed Ni / Cu electrode, a foamed Cu electrode, and a Cu sheet electrode. In a preferred embodiment, the main electrode is a foamed Ni / Cu electrode, and the weight ratio of Ni to Cu can be (1000-10):1. The main electrode has good stability and catalytic ability, which is conducive to the long-term stable activation of the magnetic composite metal oxide particles, so that the electrocatalytic composite electrode has high catalytic activity, stability and long life.

[0036] The magnet 2 may be a common material capable of generating a magnetic field, for example, at least one selected from NdFeB, AlNiCo, and SmCo5.

[0037] The electrocatalytic composite electrode disclosed in the present invention is used for electrocatalytic reaction and is used in conjunction with an electrolytic cell. Figure 2, the magnet 2 is an annular magnet, the main electrode 1 is an annular electrode matching the shape of the annular magnet, and the annular electrode is located on the inner side of the annular magnet. This embodiment is particularly suitable for a cylindrical electrolytic cell, the annular magnet surrounds the outside of the electrolytic cell, the main electrode is placed inside the electrolytic cell and can be firmly adsorbed on the inner wall of the electrolytic cell by the annular magnet, which is conducive to the full progress of the electrocatalytic reaction and improves the catalytic activity and life of the electrocatalytic composite electrode.

[0038] In a second aspect of the present disclosure, a method for preparing the electrocatalytic composite electrode according to the first aspect of the present disclosure is provided, the method comprising the following steps S1 to S3:

[0039] S1. Obtaining a magnet, a main electrode and magnetic composite metal oxide particles respectively;

[0040] S2, attaching the magnet to the outside of the electrolytic cell, and placing the main electrode at the same position inside the electrolytic cell, so that the main electrode is adsorbed on the inner wall of the electrolytic cell by the magnetic force of the magnet;

[0041] S3. Adding the magnetic composite metal oxide particles and the solvent into the electrolytic cell, and allowing the magnetic composite metal oxide particles to be adsorbed on the surface of the main electrode by the magnetic force of the magnet under stirring conditions.

[0042] In step S1, the main electrode can be purchased commercially or prepared in a laboratory. In a preferred embodiment, the main electrode is a foamed Ni / Cu electrode, which can be prepared by an electrodeposition method. Specifically, the preparation steps of the foamed Ni / Cu electrode may include: using a foamed nickel sheet as a working electrode, a reference electrode as a silver / silver chloride electrode or a saturated calomel electrode, and a counter electrode as a platinum sheet or a carbon rod, and performing an electrodeposition reaction in an electrodeposition solution. After the reaction is completed, the foamed nickel sheet is taken out, repeatedly washed with deionized water and ethanol for multiple times, and then placed in the air to dry.

[0043] Wherein, the electrodeposition solution contains copper ions, sulfuric acid and tetrabutylammonium fluoride. Further, in the electrodeposition solution, the molar concentration of the copper ions can be 1 to 10 mmol / L; the molar concentration of sulfuric acid can be 1 to 15 mmol / L; the molar concentration of tetrabutylammonium fluoride can be 0.5 to 4 mmol / L. The conditions of the electrodeposition reaction may include: a voltage of -0.2V to -1.0V vs. RHE, and a reaction time of 90 to 900s. Further, the nickel foam sheet can be pretreated before the electrodeposition reaction; wherein, the pretreatment may include soaking and ultrasonic washing the nickel foam sheet with an inorganic acid (such as hydrochloric acid) and / or an organic solvent (such as acetone), then rinsing the residual reagents with deionized water and drying it; the ultrasonic washing time can be 15 to 30 minutes, and the drying method can be selected to be natural air drying at room temperature or vacuum drying.

[0044] In step S1, the magnetic composite metal oxide particles can be prepared in a laboratory. Specifically, the preparation steps of the magnetic composite metal oxide particles may include:

[0045] Obtain a mixed solution containing metal ions, wherein the metal ions include Fe 3+ 、Co 2+ and metal M ions, M being Cr, Mn, Ni or Cu;

[0046] The mixed solution is heat-treated to obtain magnetic composite metal oxide particles.

[0047] Furthermore, the mixed solution also contains an auxiliary agent, which can be used to adjust pH, promote crystal growth, and improve the dispersibility of metal ions in the mixed solution; the molar ratio of the metal ion to the auxiliary agent can be 1: (0.1-6); the auxiliary agent can be at least one selected from urea, sodium dodecyl sulfate, ammonium chloride and sodium sulfate. In the mixed solution, the total concentration of the metal ions can be 1-40 mmol / L. In one embodiment, the metal ions include Fe 3+ 、Co 2+ and Cr 3+ , the Fe 3+ 、Co 2+ Cr 3+ The molar ratio of can be (1-4): (1-4): 1, preferably 1: 1: 1. The anions in the mixed solution can be various anions commonly used in the art, such as Cl-, Br - 、NO3 - 、SO4 - The mixed solution can be prepared in the laboratory, for example, by dissolving a suitable amount of metal salt in deionized water and adding a dispersant to obtain the mixed solution.

[0048] The heat treatment conditions may include: a temperature of 110 to 200° C. and a time of 2 to 24 hours, and the heat treatment may be performed in a polytetrafluoroethylene-lined autoclave. After the heat treatment, the solid particles may be naturally cooled to room temperature, and the solid particles may be washed several times with ethanol and water, respectively, and dried at room temperature for 12 to 48 hours to obtain magnetic composite metal oxide particles.

[0049] In step S3, the solvent may be a common organic solvent, such as ethanol, methanol, isopropanol, dichloromethane, etc. The amount of the solvent may be adjusted within a wide range, for example, the weight ratio of the magnetic composite metal oxide particles to the solvent may be 1:(100-1000). The stirring speed may be 100-800 rpm.

[0050] In a third aspect of the present disclosure, there is provided application of the electrocatalytic composite electrode described in the first aspect of the present disclosure in electrocatalytic production of ammonia.

[0051] In one embodiment, reference Figure 2 The electrocatalytic ammonia production reaction is carried out in an H-type electrolytic cell, which includes an anode area and a cathode area. The cathode area is provided with the electrocatalytic composite electrode and a reference electrode 4, and the anode area is provided with a counter electrode 5. The anode area and the cathode area are separated by a cation exchange membrane 6. The anode area and the cathode area contain an electrolyte solution and are respectively provided with a magneton 7. The electrolyte solution can be a solution containing 0.1-0.5 mol / L sodium hydroxide or potassium hydroxide, and 0.1-0.5 mol / L sodium nitrate or potassium nitrate. The voltage of the electrolytic reaction process can be -0.2 to -0.8 V (relative to the reversible hydrogen electrode, vs. RHE). The use of the electrocatalytic composite electrode for the reaction can achieve a Faraday efficiency of more than 92%, 1400 μmol·h -1 cm -2 The above NH3 yield and high stability under continuous electrolysis for more than 20h.

[0052] The disclosed electrocatalytic composite electrode uses a magnet to uniformly and tightly adsorb magnetic composite metal oxide particles on the main electrode surface, thereby bringing more catalytic active sites, having good electrocatalytic activity, stability and long catalytic life, and having a simple preparation process, low cost and broad market application prospects. The electrocatalytic composite electrode is applied to the electrocatalytic nitrate reduction ammonia synthesis reaction, paving the way for the design and preparation of nitrate reduction ammonia catalysts in the future, and has great application value in the synthesis of ammonia industrial products.

[0053] The present disclosure is further illustrated by the following examples.

[0054] In the following examples, unless otherwise specified, all reagents used are commercially available chemical reagents and there are no particular limitations thereto.

[0055] The lattice structure of the electrocatalytic composite electrode prepared in the embodiment was detected by X-ray diffraction method. The test conditions were: range 5°~70°, scan rate 5°min -1 .

[0056] The particle size of the magnetic composite metal oxide particles was detected by a scanning electron microscope (SEM) method. The test conditions were: the ambient temperature was controlled at 22-25° C., the relative humidity was less than 70%, and the samples were subjected to gold spraying before the test.

[0057] The calculation formula for the loading amount of magnetic composite metal oxide particles is: =(m-m0) / S, where m0 represents the electrode weight before the reaction (i.e., the weight of the electrode without catalyst loading), m represents the electrode weight after the reaction (i.e., the weight of the electrode loaded with catalyst), and S represents the electrode area of ​​the catalyst loading part.

[0058] Example 1

[0059] (1) Take a 200 μm thick nickel foam sheet and cut it into a 2×15 cm rectangle. Use acetone and 6 mol / L hydrochloric acid solution to ultrasonically clean it for 15 min each. Then rinse the surface of the nickel foam sheet repeatedly with deionized water and ultrasonically clean it in deionized water for 15 min. Finally, dry it at room temperature for later use.

[0060] Weigh 0.125 g CuSO4·5H2O, 0.0261 g tetrabutylammonium fluoride, and 27.2 μL concentrated sulfuric acid, add them to 100 mL deionized water, and continue ultrasonication for 20 min until the solid is completely dissolved to obtain an electrodeposition solution, in which Cu 2+ The concentration is 5mmol / L, the concentration of sulfuric acid is 5mmol / L, and the concentration of tetrabutylammonium fluoride is 1mmol / L. The electrodeposition reaction is carried out in the above-prepared electrodeposition solution. The reaction process adopts a three-electrode system for electrodeposition reaction. The working electrode is a nickel foam sheet, the reference electrode is a saturated calomel electrode, and the counter electrode is a platinum sheet. The working voltage is -0.6 V vs. saturated calomel electrode, and the reaction time is 600s. After the reaction is completed, the copper-loaded nickel foam is taken out, repeatedly washed with deionized water and ethanol for many times, and placed in the air to dry to obtain a foam Ni / Cu electrode with a weight ratio of Ni to Cu of 110:1.

[0061] (2) 0.135 g FeCl3·6H2O, 0.118 g CoCl2·6H2O, 0.196 g Cr2(SO4)3, 0.090 g urea, and 0.1458 g sodium dodecyl sulfate were added to 50 mL deionized water and stirred for 30 min until the solids were completely dissolved to obtain a mixed solution. 3+ The concentration is 10mmol / L, Co 2+ The concentration is 10mmol / L, Cr 3+ The concentration is 10mmol / L, Fe 3+ 、Co 2 + Cr 3+ The molar ratio is 1:1:1, and the molar ratio of metal ions to additives is 1:0.75. The mixed solution is poured into a 100 ml polytetrafluoroethylene-lined autoclave and heat treated at 160 ° C for 8 hours. After the heat treatment, the autoclave is naturally cooled to room temperature. The obtained solid particles are repeatedly rinsed with ethanol and water, and then dried at room temperature for 12 hours to obtain magnetic FeCoCrO4 particles.

[0062] (3) A ring magnet (made of NdFeB) is placed outside the cathode end of the H-type electrolytic cell, and a foamed Ni / Cu electrode is bent and placed inside the cathode end of the H-type electrolytic cell, and the foamed Ni / Cu electrode is fixed by the magnetic force of the magnet.

[0063] (4) Weigh 0.3 g of magnetic FeCoCrO4 particles into 50 mL of ethanol, add it to the cathode end of the electrolytic cell, and adsorb the magnetic FeCoCrO4 particles on the surface of the foamed Ni / Cu electrode under stirring at 600 rpm to obtain the electrocatalytic composite electrode prepared in this example. The XRD spectrum of the electrode is shown in FIG. Figure 3 The content of the magnetic FeCoCrO4 particles loaded is 6.5 mg / cm 2 , the particle size is 70~100nm.

[0064] Example 2

[0065] An electrocatalytic composite electrode was prepared according to the method of Example 1, except that in step (4), 0.08 g of magnetic FeCoCrO4 particles were weighed into 50 mL of ethanol and added to the cathode end of the electrolytic cell.

[0066] The content of magnetic FeCoCrO4 particles loaded on the electrode is 1.5 mg / cm 2 , the particle size is 70~100nm.

[0067] Example 3

[0068] An electrocatalytic composite electrode was prepared according to the method of Example 1, except that in step (4), 0.7 g of magnetic FeCoCrO4 particles were weighed into 50 mL of ethanol and added to the cathode end of the electrolytic cell.

[0069] The content of magnetic FeCoCrO4 particles loaded on the electrode is 18 mg / cm 2 , the particle size is 70~100nm.

[0070] Example 4

[0071] An electrocatalytic composite electrode was prepared according to the method of Example 1, except that in step (2), 0.135 g FeCl3·6H2O, 0.179 g CoCl2·6H2O, 0.099 g Cr2(SO4)3, 0.12 g urea, and 0.190 g sodium dodecyl sulfate were weighed and added to 50 mL deionized water, and stirred for 30 min until the solid was completely dissolved to obtain a mixed solution, wherein Fe 3+ The concentration is 10mmol / L, Co 2+ The concentration is 15mmol / L, Cr 3+ The concentration is 5mmol / L, Fe 3+ 、Co 2+ Cr 3+ The molar ratio is 2:3:1, and the molar ratio of metal ions to dispersing aids is 1:0.75.

[0072] The electrode supports the magnetic FeCo 1.5 Cr 0.5 The content of O4 particles is 5.7mg / cm 2 , the particle size is 70~100nm.

[0073] Example 5

[0074] An electrocatalytic composite electrode was prepared according to the method of Example 1, except that in step (2), 0.135 g FeCl3·6H2O, 0.118 g CoCl2·6H2O, 0.121 g Cu(NO3)2·6H2O, 0.090 g urea, and 0.1458 g sodium dodecyl sulfate were weighed and added to 50 mL deionized water, and stirred for 30 min until the solid was completely dissolved to obtain a mixed solution, wherein Fe 3+ The concentration is 10mmol / L, Co 2+ The concentration is 10mmol / L, Cu 2+ The concentration is 10mmol / L, the molar ratio is 1:1:1, and the molar ratio of metal ions to additives is 1:0.75.

[0075] The content of magnetic FeCoCuO4 particles loaded on the electrode is 0.6 mg / cm 2 , the particle size is 70~100nm.

[0076] Example 6

[0077] The electrocatalytic composite electrode was prepared according to the method of Example 1, except that in step (1), the pretreated nickel foam sheet was directly used as the main electrode, that is, no copper electrodeposition reaction was performed.

[0078] The content of magnetic FeCoCrO4 particles loaded on the electrode is 6.3 mg / cm 2 , the particle size is 70~100nm.

[0079] Example 7

[0080] An electrocatalytic composite electrode was prepared according to the method of Example 1, except that in step (3), a 2×2 cm sheet magnet was used instead of a ring magnet, and a 2×2 cm sheet foam Ni / Cu electrode was used and did not need to be bent in the electrolytic cell.

[0081] The content of magnetic FeCoCrO4 particles in the electrode is 7.1 mg / cm 2 , the particle size is 70~100nm.

[0082] Comparative Example 1

[0083] (1) Take a 200 μm thick nickel foam sheet and cut it into a 2×15 cm rectangle. Use acetone and 6 mol / L hydrochloric acid solution to ultrasonically clean it for 15 min each. Then rinse the surface of the nickel foam sheet repeatedly with deionized water and ultrasonically clean it in deionized water for 15 min. Finally, dry it at room temperature for later use.

[0084] Weigh 0.125 g CuSO4·5H2O, 0.0261 g tetrabutylammonium fluoride, and 27.2 μL concentrated sulfuric acid, add them to 100 mL deionized water, and continue ultrasonication for 20 min until the solid is completely dissolved to obtain an electrodeposition solution, in which Cu 2+ The concentration is 5mmol / L, the concentration of sulfuric acid is 5mmol / L, and the concentration of tetrabutylammonium fluoride is 1mmol / L. The electrodeposition reaction is carried out in the above-prepared electrodeposition solution. The reaction process adopts a three-electrode system for electrodeposition reaction. The working electrode is a nickel foam sheet, the reference electrode is a saturated calomel electrode, and the counter electrode is a platinum sheet. The working voltage is -0.6 V vs. saturated calomel electrode, and the reaction time is 600s. After the reaction is completed, the copper-loaded nickel foam is taken out, repeatedly washed with deionized water and ethanol for many times, and placed in the air to dry to obtain a foam Ni / Cu electrode with a weight ratio of Ni to Cu of 110:1.

[0085] (2) 0.135 g FeCl3·6H2O, 0.118 g CoCl2·6H2O, 0.196 g Cr2(SO4)3, 0.090 g urea, and 0.1458 g sodium dodecyl sulfate were added to 50 mL deionized water and stirred for 30 min until the solids were completely dissolved to obtain a mixed solution. 3+ The concentration is 10mmol / L, Co 2+ The concentration is 10mmol / L, Cr 3+ The concentration is 10mmol / L, Fe 3+ 、Co 2 + Cr 3+ The molar ratio is 1:1:1, and the molar ratio of metal ions to additives is 1:0.75. The mixed solution is poured into a 100 ml polytetrafluoroethylene-lined autoclave and heat treated at 160 ° C for 8 hours. After the heat treatment, the autoclave is naturally cooled to room temperature. The obtained solid particles are repeatedly rinsed with ethanol and water, and then dried at room temperature for 12 hours to obtain magnetic FeCoCrO4 particles.

[0086] (3) Weigh 0.3 g of magnetic FeCoCrO4 particles into 10 mL of ethanol, add 0.1 mL of Nafion 5% solution (DuPont), and stir at 600 rpm for 30 min to obtain a Nafion / FeCoCrO4 mixed slurry; apply the Nafion / FeCoCrO4 mixed slurry evenly and multiple times on the foamed Ni / Cu electrode sheet, and dry the electrode sheet in a 65°C oven for 15 min between each two coatings to finally obtain a Nafion-foamed Ni / Cu-FeCoCrO4 composite electrode. The content of magnetic FeCoCrO4 particles in the electrode is 10 mg / cm 2 , the particle size is 70~100nm.

[0087] Test Example

[0088] The electrodes prepared in the examples and comparative examples were used to electrocatalyze nitrate reduction to synthesize ammonia. The examples were used as test samples and the comparative examples were used as control samples to detect their catalytic activity and stability in the electrocatalytic nitrate reduction to synthesize ammonia reaction.

[0089] The nitrate electroreduction experiment was carried out in a double-chamber H-type electrolytic cell separated by a cation exchange membrane (Nafion 117), which used a three-electrode system connected to an electrochemical workstation for measurement. Mercury / mercury oxide electrode and platinum sheet electrode were used as reference electrode and counter electrode, respectively, and foam Ni / Cu-FeCoCrO4 magnetic assembly electrode was used as working electrode. Aqueous solution of 0.1 mol / L sodium hydroxide and 0.1 mol / L sodium nitrate was used as electrolyte. All potentials in the test were converted to reversible hydrogen electrode (RHE) as a reference scale. After the reaction was completed, the Nessler reagent method was used to detect the production of ammonia and calculate the Faradaic efficiency and yield.

[0090] The calculation method of NH3 Faradaic efficiency and NH3 yield involved in the experiment is as follows:

[0091] FE NH3 =(n×V×C NH3 ×F) / (M NH3 ×Q)×100%

[0092] NH3 yield = (V × C NH3 ) / (A×t)

[0093] Where n is the number of electrons required to transfer to generate one NH3 molecule in the reaction (n = 8 in this reaction), V is the volume of the electrolyte (in L), C NH3 is the concentration of NH3 generated (in mg / L), F is the Faraday constant (F=96485C / mol), M NH3 is the relative molecular mass of NH3 (17 g / mol), Q is the charge of the electrolytic reaction (in C), t is the time of the electrolytic reaction (in h), S is the area of ​​the working electrode (in cm 2 ).

[0094] Test parameters: The voltage was set to -0.4V (relative to the reversible hydrogen electrode, vs. RHE), the test time for each cycle was 3h, and the electrolyte in the cathode chamber was stirred at 300 rpm. The stability test was carried out for 8 cycles, each cycle was 3h, and the NH3 Faraday efficiency and yield in the cycle were tested after each cycle. At the same time, a new electrolyte was replaced and the next cycle test was carried out using the same working electrode. The test results are shown in Tables 1 and 2.

[0095] As can be seen from Tables 1 and 2, in the 8-cycle (24h) reaction, the comparative example 1 showed a significant decrease in the catalytic activity of catalyzing the reduction of nitrate to ammonia, and black catalyst powder was found to fall off at the bottom of the electrolytic cell. The electrocatalytic composite electrodes prepared in Examples 1 to 7 showed high stability in terms of NH3 Faraday efficiency and NH3 yield, and there was no catalyst shedding, and the catalytic life was long.

[0096] Table 1

[0097]

[0098] Table 2

[0099]

[0100]

[0101] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0102] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0103] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. An electrocatalytic composite electrode, characterized in that: The electrocatalytic composite electrode comprises a main electrode, a magnet located on one side of the main electrode, and magnetic composite metal oxide particles located on the other side of the main electrode, wherein the magnetic composite metal oxide particles are adsorbed on the surface of the main electrode by the magnetic force of the magnet; the chemical formula of the magnetic composite metal oxide particles is Fe a Co b M c O4, wherein M is Cr, Mn, Ni or Cu, and a+b+c=3.

2. The electrocatalytic composite electrode according to claim 1, wherein: The M is Cr, a=b=c=1.

3. The electrocatalytic composite electrode according to claim 1, wherein: Based on the unit area of ​​the main electrode, the content of the magnetic composite metal oxide particles is 1 to 30 mg / cm 2 .

4. The electrocatalytic composite electrode according to claim 3, wherein: Based on the unit area of ​​the main electrode, the content of the magnetic composite metal oxide particles is 3-10 mg / cm 2 .

5. The electrocatalytic composite electrode according to claim 1, wherein: The main electrode is at least one selected from a foamed Ni electrode, a Ni sheet electrode, a foamed Ni / Cu electrode, a foamed Cu electrode and a Cu sheet electrode.

6. The electrocatalytic composite electrode according to claim 1, wherein: The magnet is an annular magnet, the main electrode is an annular electrode matching the shape of the annular magnet, and the annular electrode is located inside the annular magnet.

7. A method for preparing an electrocatalytic composite electrode according to any one of claims 1 to 6, characterized in that: The method includes: respectively obtaining a magnet, a main electrode and magnetic composite metal oxide particles; Attaching the magnet to the outside of the electrolytic cell, and placing the main electrode at the same position inside the electrolytic cell, so that the main electrode is adsorbed on the inner wall of the electrolytic cell by the magnetic force of the magnet; The magnetic composite metal oxide particles and a solvent are added into the electrolytic cell, and under stirring conditions, the magnetic composite metal oxide particles are adsorbed on the surface of the main electrode by the magnetic force of the magnet.

8. The method according to claim 7, wherein: The preparation steps of the magnetic composite metal oxide particles include: Obtain a mixed solution containing metal ions, wherein the metal ions include Fe 3+ 、Co 2+ and metal M ions, M being Cr, Mn, Ni or Cu; The mixed solution is heat-treated to obtain magnetic composite metal oxide particles.

9. The method according to claim 8, wherein: The mixed solution further contains an auxiliary agent, wherein the molar ratio of the metal ion to the auxiliary agent is 1:(0.1-6); the auxiliary agent is at least one selected from urea, sodium dodecyl sulfate, ammonium chloride and sodium sulfate; In the mixed solution, the total concentration of the metal ions is 1 to 40 mmol / L; The heat treatment conditions include: temperature of 110-200° C. and time of 2-24 hours.

10. Use of the electrocatalytic composite electrode according to claims 1 to 6 in electrocatalytic production of ammonia.